Nevertheless She Persisted? Gender Peer Effects in Doctoral STEM Programs - Bostwick, Valerie K.; Weinberg, Bruce A. (Journal of Labor Economics, 2022)
We study the effects of peer gender composition in STEM doctoral programs on persistence and degree completion. Leveraging unique new data and quasi-random variation in gender composition across cohorts within programs, we show that women entering cohorts with no female peers are 11.7pp less likely to graduate within 6 years than their male counterparts. A 1 sd increase in the percentage of female students differentially increases women's probability of on-time graduation by 4.4pp. These gender peer effects function primarily through changes in the probability of dropping out in the first year of a Ph.D. program.